IMPLEMENTASI MULTIMEDIA INTERAKTIF BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD - Rusfriyanti, Rindy Berinda; Rondli, Wawan Shokib (Universitas Negeri Surabaya, 2023)
Learning in elementary schools should be an interesting learning and can improve student learning outcomes. But in fact what happens is student learning outcomes are still low. This also happened to third grade students at an elementary school in Jepara Regency. This study aims to improve student learning outcomes in third grade elementary schools through learning with interactive multimedia based on local wisdom. This research is a classroom action research using the Elliot model which consists of three cycles, each cycle consisting of three actions. Data collection techniques used were tests, observations, field notes, interviews and documentation. The results showed that student learning outcomes had increased, the average value in cycle I is 50.11, cycle II is 70.18, and cycle III is 80.76. Thus learning with interactive multimedia based on local wisdom can improve the learning outcomes of elementary school students.